2016
DOI: 10.1002/jssc.201600350
|View full text |Cite
|
Sign up to set email alerts
|

Model‐based analysis of a dielectrophoretic microfluidic device for field‐flow fractionation

Abstract: We present the development of a dynamic model for predicting the trajectory of microparticles in microfluidic devices, employing dielectrophoresis, for Hyperlayer field-flow fractionation. The electrode configuration is such that multiple finite-sized electrodes are located on the top and bottom walls of the microchannel; the electrodes on the walls are aligned with each other. The electric potential inside the microchannel is described using the Laplace equation while the microparticles' trajectory is describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Combining Eqs. (11) and (12), we are able to describe the iterative method for particle tracing as follows [40]: r n+1 = 2r n r n 1 + 0:5 F n m dt 2 :…”
Section: Particle Tracing Methodsmentioning
confidence: 99%
“…Combining Eqs. (11) and (12), we are able to describe the iterative method for particle tracing as follows [40]: r n+1 = 2r n r n 1 + 0:5 F n m dt 2 :…”
Section: Particle Tracing Methodsmentioning
confidence: 99%
“…Cells will levitate to heights, in a DEP‐FFF separation microdevice, depending on their properties and in the process achieve separation. The height to which a cell levitates depends on properties such as conductivity, permittivity, and density of the medium and the cell .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the numerical simulation of DEP microfluidic devices, Matthew et al. conducted a study to investigate the effect of various parameters on the performance of a numerically simulated DEP device. It was concluded that the microchannel depth, electrode spacing lengths, and voltage affect the levitation height of the microparticles and the flow rate and microparticle radius were not influential.…”
Section: Introductionmentioning
confidence: 99%
“…Among the applications that computational simulations of microfluidic devices can help are blood-related separation purposes [15,16], cell separation procedures [17,18], and mixing [19,20]. Regarding the numerical simulation of DEP microfluidic devices, Matthew et al [21] conducted a study to investigate the effect of various parameters on the performance of a numerically simulated DEP device. It was concluded that the microchannel depth, electrode spacing lengths, and voltage affect the levitation height of the microparticles and the flow rate and microparticle radius were not influential.…”
Section: Introductionmentioning
confidence: 99%